Influence of different chemical treatments on the surface of Al2O3/ZrO2 nanocomposites during biomimetic coating. Issue 5 (1st April 2017) - dos Santos, Kátia Helena; Ferreira, Julieta Adriana; Osiro, Denise; da Conceição, Gelson José Andrade; Filho, Rubens Bernardes; Colnago, Luiz Alberto; de Jesus Agnolon Pallone, Eliria Maria
Abstract: The objective of this study is to evaluate the influence of different chemical surface treatments (H3 PO4, HNO3, and NaOH) in the formation of calcium phosphate phases on the surface of Al2 O3 /ZrO2 (5 vol%) nanocomposite. For this purpose, Al2 O3 /ZrO2 samples were shaped, calcined at 400 °C, sintered at 1500 °C, subjected to different chemical treatments, and biomimetically coated from 14 to 21 days. Surface characterization was performed by scanning electron microscopy, atomic force microscopy, confocal microscopy, X-ray diffraction, and infrared spectroscopy. It was observed that the preliminary chemical treatment favored the formation of particular calcium phosphate phases of interest, such as α-TCP (alpha-tricalcium phosphate), β-TCP (beta-tricalcium phosphate), and HA (hydroxyapatite). The differences among the percentages of the phases formed affected the homogeneity of calcium phosphate distribution within the nanocomposites as well as the roughness of the formed layer, effectively contributing to adhesion, proliferation, and desired cell biofixation on bone implant.